Quaternary β2, 2-amino acid derivatives by asymmetric addition of isoxazolidin-5-ones to para-quinone methides. Issue 4 (12th December 2019) - Eitzinger, Andreas; Winter, Michael; Schörgenhumer, Johannes; Waser, Mario
Abstract : Novel densely functionalized β 2, 2 -amino acids were obtained in almost enantiopure form using down to 20 ppm of a chiral phase-transfer catalyst. Abstract : The highly enantioselective (>99.5% ee) synthesis of a new class of densely functionalized β 2, 2 -amino acid derivatives by reacting isoxazolidin-5-ones with para -quinone methides in the presence of chiral ammonium salt phase-transfer catalysts was developed. The reaction proceeds with exceptionally low catalyst loadings down to 20 ppm on gram scale and the utilization of the primary addition products towards further manipulations was demonstrated for selected examples.